Improving the Method of Assessing Production Capacity of Textile Industry Enterprises - Isaev Ravshan Abdurakhmanovich; Yoldoshaliev Shahzodbek Farkhod Ogli (Genius Journals, 2023)
The article examines the production potential of textile industry enterprises from the point of view of analyzing the condition of its constituent elements and finding unused internal potential.
Keywords: Production capacity; capacity; method; integral assessment